2000
DOI: 10.1021/ic9910615
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Uranium Chloride Fluorides UF6-nClnand Methoxyuranium Fluorides UF6-n(OCH3)n:  A Theoretical Study of Equilibrium Geometries, Vibrational Frequencies, and the Role of the f Orbitals

Abstract: The title compounds, the uranium (VI) fluoride chlorides (UF6-nCln, n = 0-6) and methoxyuranium (VI) fluorides [UF6-n(OCH3)n, n = 0-5], have been studied using relativistic density functional theory. Applying the B3LYP hybrid functional and an effective core potential on uranium, equilibrium geometries have been calculated for these molecules. In addition, harmonic vibrational frequencies have been computed for the chloride fluorides. Calculated frequencies have been compared to experiment where possible. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 78 publications
2
37
0
Order By: Relevance
“…pounds. [7,35,60,61] Moreover, for the C 3v and C 2v structures of the molecules studied, the QR-BP/TZP geometrical parameters are very close to those obtained from the (probably most reliable) MP2 calculations, closer than the B3PW ones! Nevertheless, the above results show that the BP functional should be used with caution in actinide research.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…pounds. [7,35,60,61] Moreover, for the C 3v and C 2v structures of the molecules studied, the QR-BP/TZP geometrical parameters are very close to those obtained from the (probably most reliable) MP2 calculations, closer than the B3PW ones! Nevertheless, the above results show that the BP functional should be used with caution in actinide research.…”
supporting
confidence: 67%
“…The quadrupolar polarisation of the U electron-density distribution can also be expected on the UÀhalogen bond. We found in the literature two papers reporting the computed molecular geometry of UCl 5 F. [61,64] The authors obtained somewhat shorter UÀCl bonds trans to F with respect to the UÀCl bond trans to Cl. Depending on the level of theory used, the differences amounted to 0.4-0.8 pm.…”
Section: Inverse Trans Influencementioning
confidence: 99%
“…[17] and [18] and references therein). Batista et al [19] investigated the lower uranium fluorides, UF 5 and UF 4 , [18] in their benchmark study of the UF n bond dissociation energies (BDE).…”
Section: Previous Theoretical Workmentioning
confidence: 99%
“…While uranium hexafluoride UF 6 is one of the most extensively studied actinide molecules, 1 both experimentally and theoretically, very few computational studies have been reported on the rest of the fluoride series UF n or on the uranium chlorides UCl n .…”
Section: Introductionmentioning
confidence: 99%
“…The UF 6 molecule, even though it is the largest and has the most electrons, is the easiest one to study with ab initio calculations because of its closed shell nature. This molecule has been studied by many authors with a variety of computational techniques 1,[13][14][15][16][17][18] so that it has become a testing benchmark for computational methods aimed at actinide molecules. A study of the electronic structure of UF 4 has been reported using HartreeFock-Slater type calculations 19 with scalar relativistic pseudopotentials.…”
Section: Introductionmentioning
confidence: 99%